The behaviour features of polymer nanocomposites filled with calcium carbonate - Kozlov, Georgiy; Aphashagova, Zarema; Malamatov, Akhmed; Zaikov, Gennady (Publishing House of Lviv Polytechnic National University, 2012)
The most typical behaviour features of polymer nanocomposites filled with dispersed calcium carbonate were considered. The quantitative analysis was carried out within the frameworks of structural model: the cluster model of polymers amorphous state structure and fractal analysis. It has been shown that all changes of the considered nanocomposites properties were defined by polymeric matrix structure variations, which are due to nanofiller introduction. Розглянуті найбільш типові особливості поведінки полімерних нанокомпозитів наповнених дисперсним карбонатом кальцію. Проведено кількісний аналіз в рамках структурної моделі: кластерна модель аморфної структури полімерів і фрактальний аналіз. Показано, що всі зміни у властивостях розглянутих нанокомпозитів визначені зміною структури полімерної матриці через введення нанонаповнювача.
Особливості поведінки наповнених карбонатом кальцію полімерних нанокомпозитів
Keywords: polymer; nanocomposite; elasticity modulus; interfacial adhesion; yield; plasticity; fractal analysis; полімер; нанокомпозит; модуль пружності; міжфазова адгезія; пластичність; фрактальний аналіз